Cyclical wages in a search-and-bargaining model with large firms - Julio J. Rotemberg (Federal Reserve Bank of Boston, 2006)
This paper presents a complete general equilibrium model with flexible wages, where the degree to which wages and productivity change when cyclical employment changes is roughly consistent with postwar U.S. data. Firms with market power are assumed to bargain simultaneously with many employees, each of whom finds himself matched with a firm only after a process of search. When employment increases as a result of reductions in market power, the marginal product of labor falls. This fall tempers the bargaining power of workers and thus dampens the increase in their real wages. The procyclical movement of wages is dampened further if the posting of vacancies is subject to increasing returns.
Keywords: E24; E37; J64; 330; Betriebsgröße; Marktmacht; Lohnverhandlungen; Lohnniveau; Arbeitsproduktivität; Konjunktur; Ökonometrisches Modell